Analisis Kualitas Pelayanan Publik pada Dinas Dukcapil Kabupaten Halmahera Tengah - Susrianti Susrianti; Petronela Sahetapy; Julia Theresia Patty (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
Public service quality in population administration is a strategic indicator of local bureaucratic performance because it directly affects citizens' administrative rights and trust in government. This study aims to analyze the quality of public services at the Population and Civil Registration Office of Central Halmahera Regency. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation involving the head of office, service staff, and community service users. The analysis used the SERVQUAL framework, covering tangibles, reliability, responsiveness, assurance, and empathy. The findings indicate that public service quality is generally adequate. Service facilities and infrastructure are available, procedures are implemented, officers respond to community needs, and the public feels relatively safe and confident in the legality of issued documents. However, several weaknesses remain, including limited waiting-room capacity, unstable internet connectivity, and inconsistent service performance during periods of high demand. The study implies that improving population administration services requires strengthening service infrastructure, stabilizing digital systems, enhancing staff professionalism, and expanding outreach services for remote communities. These findings contribute to public administration studies by emphasizing the importance of combining service standards, technological readiness, and human-centered service culture in peripheral local government contexts.